Synthesis of Co-TiO2 Nanostructured Photo-Catalytic Coatings for MDF Substrates - Giampiccolo, Andrea
Aggregates of undoped and cobalt-doped TiO2 nanoparticles were prepared through a sol gel method followed by annealing at 450 degrees C to obtain an anatase structure. The resulting aggregates were characterized using field emission scanning electron microscopy, scanning electron microscopy with energy dispersive X-ray analysis and Raman spectroscopy. Photocatalytic (PC) activity of the annealed nanostructures was evaluated through monitoring the degradation of a methylene blue solution containing the aggregated nanoparticles and comparisons made to compare to pure TiO2 (P25) and carbon doped TiO2 (Kronoclean 7000). Degradation under UV radiation (375-385nm), green light (525-535nm) and white light (5200K) was determined quantitatively using a UV-Vis spectrophotometer to measure the decreasing intensity of the blue colour. The Co-TiO2, Kronoclean 7000 and undoped nanoparticles were then applied to the surface of MDF substrates. Experimental results show that in all cases nanostructured particles aggregated to form micro-grains. Furthermore the photocatalytic activity tests indicated a change in the band gap of the Co-doped particles since the photocatalytic activity was greater under visible light compared to a pure TiO2. Preliminary tests on the coatings indicated photocatalytic activity in all the substrates studied. The results suggest that the incorporation of Co-doped TiO2 nanoparticles in coatings has the potential for improving indoor air quality by decomposing volatile organic compounds (VOCs) using both visible and UV light.